Power and law in international society : international relations as the sociology of international law - Klamberg, Mark (Abingdon, Oxon : Routledge, 2015)
'This book assesses how international law and its institutions may be relevant and influence the course of international relations, in other words the relationship between power and law. This is done in relation to five regimes; international trade, environmental protection, human rights, criminal justice and use of force.The majority of international law literature focuses on the content of international rules (i.e. regimes) but has a tendency to ignore why these regimes exist and to what extent the rules actually affect state behaviour. The assumption is that states follow international law when the reality sometimes tells us differently. Turning to international relations literature, some scholars as represented in their publications focus on theories based on the distribution of power among states and ignore the existence and relevance of international law. In contrast, Power and Law in International Society examines theories of international relations, international law and formal institutions as well as an account of empirical research on the relevance of international law for the behaviour of states.This book has three main themes. First, the book will explain the foundations of international society from an inter-disciplinary perspective relaying on legal studies as well as international relations. Second, the book will examine variations in the degree of legalization in terms of obligation, precision, delegation and state acceptance. Finally, the book will give an account of the empirical research on the relevance of international law for the behaviour of states. This book will be of great interest to scholars of international law and international relations.'--
'When examining international law there is a risk to focus on the content of international rules (i.e. regimes) but ignore why these regimes exist and to what extent the rules affect state behaviour. Concurrently, when studying international relations there is a risk to focus on theories based on the distribution of power among states, and to overlook the existence and relevance of international law. These risks both hold their dangers. The overlooking of international relations risk assuming that states follow international law, and conversely a discounting of international law makes it difficult for readers to understand international regimes and their rules in more than a superficial manner. The book works to unify international law and international relations by exploring how international law and its institutions may be relevant and influence the course of international relations in international trade, environmental protection, human rights, criminal justice and the use of force. As a book on the intersection of power and law, this book will be of great interest and use to scholars and students of international law, international relations, politics and international trade, and conflict resolution'--
International law as a leap of faith? -- Approaches to international regimes, power and law -- International trade -- Environmental protection -- Human rights -- International criminal justice -- Use of force -- Reconciling international law and international relations.
Includes bibliographical references (pages 163-178) and index.
Keywords: International law -- Sociological aspects; International relations